Turning Challenges into Opportunities: The Role of Leadership Qualities in Adopting Social Entrepreneurship Initiatives during COVID-19 - Basit, Abdul; Ejaz, Shaffaq (iRASD Journal of Management, 2023)
Social entrepreneurship (SE) can spark positive societal change by providing adequate and long-term solutions to global issues. In the context of the COVID-19 pandemic, traditional businesses have been impacted on micro and macro levels. However, SE can ensure social welfare, job creation, and economic improvement. This study examines the impact of Paradoxical Leadership, Transformational Leadership, and Entrepreneurial Leadership on SE during the pandemic, specifically in the pharmaceutical and textile manufacturing sectors of Punjab, Pakistan. The study also investigates the moderating role of Public Service Motivation (PSM) between these leadership styles and SE. The findings suggest that leadership qualities positively impact SE during COVID-19, and PSM plays a moderating role in the relationship between leadership styles and SE in the manufacturing sector. The results of this study could inform the development of effective leadership strategies for social entrepreneurs during global crises.